Use of planar covariation in lower limb kinematics to characterize adaptations of running after cycling in elite triathletes - Walsh, Joel A.; Stamenkovic, Alexander; Dawber, James P.; Stapley, Paul J. (Frontiers in Sports and Active Living, 2023)
Purpose To characterize alterations of lower limb intersegmental coordination during the acute phase of running after cycling among highly trained triathletes using an analysis of planar covariation. Methods Nine highly trained triathletes completed a control run (CR) and a run after transitioning from cycling exercise (transition run, or TR condition) on a motorized treadmill at a self-selected pace. Sagittal plane kinematics were recorded using a 3D Vicon motion capture system. Intersegmental coordination of the thigh, shank and foot segments of the right lower limb and run loop planarity were calculated during running before cycling and at four different times after the end of cycling. Results PCA showed a significant within-subject phase shift of the run loop planarity (F = 6.66, P = 0.01). Post hoc analysis showed significance median differences increase for u3t parameter between CRSS vs. TR30 (P = 0.01), TRt1/2 (P = 0.01) and TRMRT (P = 0.01). No difference for u3t parameter existed between CRSS vs. TRSS. Conclusion Prior variable-cadence, moderate intensity cycling has a significant effect on run loop planarity and therefore intersegmental coordination during the acute transition phase among highly trained triathletes. However, alterations to lower limb coordination are corrected by the 3rd minute after the beginning of the post cycle run. We suggest that planar covariation can be used as a more sensitive measure of cycling-induced variations in running to characterize adaptation in elite and importantly, developing athletes.